Geheimnisvolle Gräben am Nübeler Noor - Fichte, Almut (Arkæologi i Slesvig-Archäologie in Schleswig, 2023)
In 2018, a trial trench near an offshoot of the Flensburg Fjord revealed a row of three partly parallel linear ditches. Adjoining one of those ditches was a much thinner palisade ditch, another few smaller ditches, as well as a settlement. The buildings of the settlement had the same direction as the parallel ditches and date mainly to the late Roman Iron Age, around the same time as the large depositions of weaponry in the nearby situated Nydam bog. The construction of the parallel ditches seems to date to the middle of the Bronze Age, around the same time as an extensive cultural shift happened throughout most of Europe. However, they also seem to have layers from the pre-Roman Iron Age and a top layer, and thus closure, which is contemporary with the settlement traces of the late Roman Iron Age. Until now, no other similar Bronze Age structures are known from the Danish area. There are no contemporary settlements nearby and the original function of the ditches is still unclear. Very similar structures are known from Germany and in great number from the United Kingdom. Here they are often accompanied by pit rows, which may be the case in Nübel too. The parallel ditches, however, are not the only fascinating aspect of this site. Some of the nearby situated smaller ditches, as well as a large depositional layer, seem to date to the mid Neolithic, just as a nearby circular structure may date to the Neolithic Period. A fortified manor and a church show that the site was also settled during the Medieval Period, though presumably unaware of the much older ditches.